Electrospun Nanofiber Poly (3,4-ethylenedioxytriophene): poly (styrene sulfonate) / poly (vinyl alcohol) as Strain Sensor Application - Chotimah Chotimah; Aditya Rianjanu; Bimo Winardianto; Misbachul Munir; Indriana Kartini; Kuwat Triyana (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Institut Teknologi Sumatera, Lampung Selatan, Lampung, Indonesia, 2021)
A strain sensor based on poly (3,4-ethylenedioxytriophene): poly (styrene sulfonate)/poly (vinyl alcohol) (PEDOT: PSS/PVA) nanofiber has been successfully fabricated by electrospinning technique. Patterned copper wires were deposited on the mica flexible substrate with the distance of 1 mm. The sensor then characterized with various strain by one side bending. The conductivity of as-spun nanofiber mats can be adjusted from 0.03 to 1.2 µS cm-1 with various concentration of PVA and depends on its structure and its nanofiber diameter. The sensing mechanism of nanofiber-based strain sensor is due to the common piezoelectric effect of PEDOT:PSS polymer and unique nanostructure of nanofiber mats. When the sensor stretched, the length of nanofiber increase affecting the geometrical change and lead the increasing in resistance. This sensor shows good repeatability with gauge factor of 17. The performance of PEDOT:PSS/PVA nanofiber based strain sensor make nanofiber mats as promising alternative materials for strain sensor application.